Three Ingredients of Safflower Alleviate Acute Lung Injury and Inhibit NET Release Induced by Lipopolysaccharide - Yun-peng Wang; Yu Guo; Ping-shan Wen; Zhen-zhen Zhao; Jian Xie; Kai Yang; Qing Yang; Jia-feng Wang; Xiao-ming Deng (Mediators of Inflammation)
Xuebijing injection is a Chinese herb compound to treat sepsis in China, but it contains many different kinds of components, and each component may have different effects in treating sepsis. The present study was performed to investigate the effect of three ingredients of Xuebijing, safflor yellow A (SYA), hydroxysafflor yellow A (HSYA), and anhydrosafflor yellow B (AHSYB), in lipopolysaccharide- (LPS-) induced acute lung injury (ALI). LPS (10 mg/kg) was injected intratracheally to induce acute lung injury in mice, which were then treated with SYA, HSYA, and AHSYB. The blood, bronchoalveolar lavage fluid (BALF), and lung tissues were collected to detect degree of lung injury, level of inflammation, and neutrophil extracellular traps (NETs). In vitro experiments were performed using HL-60 cells stimulated with phorbol myristate acetate (PMA). Lung injury induced by LPS was alleviated by SYA, HSYA, and AHSYB as demonstrated by the histopathologic test. The three components inhibit LPS-induced elevation of the levels of inflammatory factors and wet-to-dry weight ratio as well as the amount of protein and cells in the BALF. They also induced a remarkably less overlay of myeloperoxidase (MPO) and histone in the immunofluorescence assay and reduced level of MPO-DNA complex in plasma. The in vitro assay showed a similar trend that the three components inhibited PMA-induced NET release in neutrophil-like HL-60 cells. Western blot demonstrated that phosphorylation of c-rapidly accelerated fibrosarcoma (c-Raf), mitogen-activated protein kinase ERK kinase (MEK), and extracellular signal-regulated kinase (ERK) in the lungs of LPS-challenged mice, and PMA-treated HL-60 cells were all significantly reduced by SYA, HSYA, and AHSYB. Therefore, our data demonstrated that three components of XBJ, including SYA, HSYA, and AHSYB, showed a protective effect against LPS-induced lung injury and NET release.